Mechanochemical activation of titanium dioxide – vanadium pentoxide composite photocatalyst under conditions of high contact pressure - Sviridova, Tatsiana V.; Shcherbakova, Valentina B.; Sviridov, Dmitry V. (Journal of the Belarusian State University. Chemistry, 2026)
A new method for producing titanium dioxide – vanadium pentoxide thin-film photocatalysts based on the mechanochemical activation of a mixture of dispersed oxides under high mechanical loading has been proposed, excluding the annealing of oxide phases, is proposed. It has been established that the processes of increasing photoactivity and the appearance of photoinduced oxidation activity after preliminary irradiation observed in the case of photocatalysts obtained in this way are due to mechanochemically stimulated dispersion of oxide particles and their disordering. It is noted that these circumstances create favourable conditions for the formation of close heterooxide contacts and the formation of vanadium pentoxide polymorphs of tubular morphology, which ensure the storage of photoinduced charge.
Keywords: photocatalyst; titanium oxide; vanadium oxide; tubulenes; charge storage